Association between e-cigarette use and susceptibility to tobacco product use: findings from the 2019 China National Youth Tobacco Survey - Li, Sixuan; Zeng, Xinying; Di, Xinbo; Liu, Shiwei (Frontiers in Public Health, 2024)
Background: There is an ongoing debate whether e-cigarettes act as a gateway to tobacco smoking or contribute to smoking cessation, and relevant studies were limited among Chinese adolescents. This cross-sectional study aims to explore the relationship between the e-cigarette use and susceptibility to tobacco product use among Chinese high school students. Methods: The study population was comprised of 107,633 never smokers and 19,377 former smokers generated from China National Youth Tobacco Survey in 2019. The primary independent variables of interest were ever e-cigarette use, current e-cigarette use, and the frequency of current e-cigarette use. The main outcome was the susceptibility to tobacco product use. The multilevel logistic regression was used to estimate the association between the primary independent variables of interest and the outcome variable. Moreover, two additional multilevel logistical regression models were fitted using two alternative definitions of the outcome as the sensitivity analyses. Results: Among never smokers, students who ever used e-cigarettes were more likely to be susceptible to tobacco product use compared to students who never used e-cigarettes (AOR=2.83, 95%CI=2.59-3.08). Students who currently used e-cigarettes were more likely to be susceptible to tobacco product use than those who did not currently use e-cigarettes (AOR=3.89, 95%CI=3.21-4.72). Among former smokers, with the same settings of modeling, the AORs were 1.76 (95%CI=1.62-1.91) and 3.16 (95%CI=2.52-3.97), respectively. Similar results were obtained from the two sensitivity analyses. Conclusions: Among Chinese high school students, both never smokers and former smokers, e-cigarette use, especially current e-cigarette use, was positively associated with susceptibility to tobacco product use. It is recommended to strengthen the monitoring of e-cigarettes and to provide targeted health educations to adolescents.